1999
DOI: 10.1046/j.1365-2168.1999.00981.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of prevertebral and retrosternal gastric tube reconstruction after resection of oesophageal carcinoma

Abstract: After subtotal oesophagectomy retrosternal gastric tube reconstruction can be performed easily and safely, and gives functional results similar to those obtained with prevertebral reconstruction. In patients at high risk for developing secondary malignant dysphagia the extra-anatomical route is the reconstruction of first choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
66
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 18 publications
4
66
0
5
Order By: Relevance
“…In one randomized study, postoperative recovery, anastomotic leakage and benign stricture formation were not significantly different between the two routes of reconstruction. Functional results, as measured by scintigraphic gastric emptying, quantitative and qualitative oral food intake, and changes in body weight were also similar [5]. In contrast, two studies demonstrated a higher cardiopulmonary complication rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one randomized study, postoperative recovery, anastomotic leakage and benign stricture formation were not significantly different between the two routes of reconstruction. Functional results, as measured by scintigraphic gastric emptying, quantitative and qualitative oral food intake, and changes in body weight were also similar [5]. In contrast, two studies demonstrated a higher cardiopulmonary complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…After subtotal resection with anastomosis in the neck, there is a choice of placing the conduit in the orthotopic, retrosternal, or subcutaneous route [2, 3, 4, 5, 6]. The subcutaneous route is rarely used because it is cosmetically unsightly.…”
Section: Introductionmentioning
confidence: 99%
“…The neoesophagus is routinely positioned in the esophageal bed, i.e., in the posterior mediastinum. When the surgical resection is macroscopically irradical, and thus symptomatic locoregional tumor recurrence can be expected shortly after the operation, the retrosternal or subcutaneous route is chosen [1]. Occasionally the stomach is not available for esophageal substitution, e.g., in patients with previous gastric resection, or in those with an esophageal tumor which infiltrates the stomach well beyond the cardia precluding a tumor-free distal resection margin and thus necessitating a total gastrectomy (in addition to resection of the esophagus).…”
Section: Introductionmentioning
confidence: 99%
“…Some reports have shown no difference between the SR and PM techniques in the perioperative complications and functional outcomes (13)(14)(15). Zheng et al found a significant association (P=0.018) between anastomotic stricture and use of SR (2).…”
Section: Discussionmentioning
confidence: 99%